Jaminan Pemeliharaan Kesehatan bagi Masyarakat Miskin Kota Yogyakarta - Haeruddin Haeruddin (Jurnal Demokrasi, 2010)
This study tried to describe the health care insurance program for the poor implemented by regional health insurance provider at Yogyakarta city. A qualitative approach has been used in this study. The finding of this study indicated that the successful implementation and development of the care program provides benefits to the government. The successful of the program includes (1) development budget expenditure in the health sector be more efficient, (2) partial subsidies can be allocated to communities in need (3) government get people healthier and more productive. Nevertheless, the fact in Indonesia nowadays, also in Yogyakarta, the development of Managed Care Program still runs slowly. Kata Kunci : Jaminan Kesehatan, Masyarakat Miskin, Unit Pelaksana Teknis (UPT)